Awareness of E-Cigarettes among Student in Malaysian Public University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: The intention of this research is to develop understanding of e-cigarette awareness towards students in university. Method: The data collection method used in this study is online survey using Google form applications via social media platforms. The respondents consist of 304 students from Malaysian public university located in north Malaysia. This survey consists of 14 questions including the demographic question. Result: Most of the respondents (n = 304) were aware of the impact of e-cigarettes and 124 (40.79 percent) had used an e-cigarette previously. E-cigarette awareness is also high among female students compared to male students.Conclusion: Importantly, attention needs to be paid to the use of e-cigarettes. Besides that, government law enforcement needs to be restructured to monitor the e-cigarette product from direct to adult access. Institutions also need to play a role in exposing students to awareness of e-cigarettes by increasing awareness programs. Overall, this study suggests a further research on this area to be conducted in a large scope of population in Malaysia and demographic locations.